Nonimaging High Concentrating Photovoltaic System Using Trough - Waseem Iqbal; Irfan Ullah; Seoyong Shin (Energies, 2023)
Solar energy is a long-established technology, which has zero CO2 emissions, and provides low-cost energy for a given area of land. The concentrator photovoltaic (CPV) has been given preference over the photovoltaic due to its high efficiency. In a CPV system, most of the solar cell area has been replaced with an optical concentrator. Various parabolic trough based CPV systems have been presented where a concentration of <300 is achieved. In the current research, a design is presented to achieve a high concentration of 622×. The design consists of two stages of concentration including parabolic trough as a main concentrator and nonimaging reflective grooves as a secondary concentrator. The trough reflects the incident light towards the secondary reflector where the light is redirected over the solar cell. Design of the two-stage concentrator, ray-tracing simulation, and results are presented. The system achieved an optical efficiency of 79%. The system would also be highly acceptable in solar thermal applications owing to its high concentration.